SEWING WASTE AND ITS RATIONAL USE - Исматуллаева Холида Закруллаевна; Мухитдинова Нодира (Web of Journals Publishing, 2025)
The causes of the occurrence and rational use of waste in the clothing industry is currently especially relevant. Inter-lunges and end waste of materials formed as a result of cutting products of the main assortment are proposed to be used for the production of goods of folk applied art.
Keywords: fibrous waste, use, ecology, waste disposal, preparatory operations, methods of use.